Analisis Yuridis Pemutusan Perjanjian Secara Sepihak - Nugrah Gables Manery (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to examine the analysis of unilateral contract termination. The method used in this study is normative juridical. The approaches used in this study are the statutory approach and the conceptual approach. The results of this study indicate that the provisions for contract termination as stipulated in Article 1338 paragraph (2) of the Civil Code should not override the provisions of Article 1266 of the Civil Code, which governs the conditions for annulment in reciprocal agreements. Termination clauses in contracts are generally unilateral, disregarding the provisions of Article 1266 of the Civil Code. The Civil Code does not explicitly regulate the distinction between damages resulting from breach of contract and damages resulting from unlawful acts. Therefore, what is needed is a clear understanding of the concept of contract termination, so that in the future there will be regulations that provide legal certainty to the parties involved.